Combination therapy protects macaques against advanced Marburg virus disease - Cross, Robert W.; Bornholdt, Zachary A.; Prasad, Abhishek N.; Borisevich, Viktoriya; Agans, Krystle N.; Deer, Daniel J.; Abelson, Dafna M.; Kim, Do H.; Shestowsky, William S.; Campbell, Lioudmila A.; Bunyan, Elaine; Geisbert, Joan B.; et al. (Nature communications, 2021)
Monoclonal antibodies (mAbs) and remdesivir, a small-molecule antiviral, are promising monotherapies for many viruses, including members of the genera Marburgvirus and Ebolavirus (family Filoviridae ), and more recently, SARS-CoV-2. One of the major challenges of acute viral infections is the treatment of advanced disease. Thus, extending the window of therapeutic intervention is critical. Here, we explore the benefit of combination therapy with a mAb and remdesivir in a non-human primate model of Marburg virus (MARV) disease. While rhesus monkeys are protected against lethal infection when treatment with either a human mAb (MR186-YTE; 100%), or remdesivir (80%), is initiated 5 days post-inoculation (dpi) with MARV, no animals survive when either treatment is initiated alone beginning 6 dpi. However, by combining MR186-YTE with remdesivir beginning 6 dpi, significant protection (80%) is achieved, thereby extending the therapeutic window. These results suggest value in exploring combination therapy in patients presenting with advanced filovirus disease. Extending the therapeutic window for acute viral infections could save lives. Here, the authors show that combination treatment with a human monoclonal antibody and remdesivir initiated at 6 days post infection with Marburg virus provides 80% protection in non-human primates.